Regulation of Immune Cell Infiltration into the CNS by Regional Neural Inputs Explained by the Gate Theory - Yasunobu Arima; Daisuke Kamimura; Lavannya Sabharwal; Moe Yamada; Hidenori Bando; Hideki Ogura; Toru Atsumi; Masaaki Murakami (Mediators of Inflammation)
The central nervous system (CNS) is an immune-privileged environment protected by the blood-brain barrier (BBB), which consists of specific endothelial cells that are brought together by tight junctions and tight liner sheets formed by pericytes and astrocytic end-feet. Despite the BBB, various immune and tumor cells can infiltrate the CNS parenchyma, as seen in several autoimmune diseases like multiple sclerosis (MS), cancer metastasis, and virus infections. Aside from a mechanical disruption of the BBB like trauma, how and where these cells enter and accumulate in the CNS from the blood is a matter of debate. Recently, using experimental autoimmune encephalomyelitis (EAE), an animal model of MS, we found a “gateway” at the fifth lumber cord where pathogenic autoreactive CD4+ T cells can cross the BBB. Interestingly, this gateway is regulated by regional neural stimulations that can be mechanistically explained by the gate theory. In this review, we also discuss this theory and its potential for treating human diseases.